Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s11894-016-0531-z
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Esophagitis From an Allergy Perspective: How to Optimally Pursue Allergy Testing & Dietary Modification in the Adult Population

Abstract: Eosinophilic esophagitis (EoE) is a clinicopathologic condition characterized by symptoms of esophageal dysfunction and eosinophil-predominant inflammation. In adults, the three most common treatment options are swallowed steroids, elimination diets, and periodic esophageal dilations. Many different elimination diets have been studied in adults, including elemental diets, allergy testing-directed diets, and empiric elimination diets. This article will review the existing data on these dietary therapies and wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…While allergen-specific IgE antibodies are also often detected, elimination diets based solely on IgE sensitization have had mixed success 31,32 , and the use of anti-IgE treatment was not shown to be more efficacious in inducing EoE remission than placebo 29 . It has been shown, in both pediatric and adult populations, however, that food is a key trigger for EoE 33,34 . The strongest such evidence comes from trials with elemental diets, where histologic remission rates greater than 90% are observed, although focused food elimination diets also often lead to remission 10,11,34 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…While allergen-specific IgE antibodies are also often detected, elimination diets based solely on IgE sensitization have had mixed success 31,32 , and the use of anti-IgE treatment was not shown to be more efficacious in inducing EoE remission than placebo 29 . It has been shown, in both pediatric and adult populations, however, that food is a key trigger for EoE 33,34 . The strongest such evidence comes from trials with elemental diets, where histologic remission rates greater than 90% are observed, although focused food elimination diets also often lead to remission 10,11,34 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…Determination of sIgE performs slightly better than SPT or ATP in predicting food triggers in EoE . Some have advocated to check for sIgE to the usual trigger foods milk, wheat, egg, soy/legumes/peanut, tree nuts, fish, and shellfish and perform targeted elimination diet in case of positive test results to one or a few foods . This approach may fail in patients with airborne EoE triggers such as swallowed pollens or pollen‐food syndrome.…”
Section: Allergy Testing In Eosinophilic Esophagitismentioning
confidence: 99%
“…49 Some have advocated to check for sIgE to the usual trigger foods milk, wheat, egg, soy/legumes/peanut, tree nuts, fish, and shellfish and perform targeted elimination diet in case of positive test results to one or a few foods. 52 This approach may fail in patients with airborne EoE triggers such as swallowed pollens or pollen-food syndrome. Based on the current performance of allergy tests, others do not recommend targeted elimination diet in EoE.…”
Section: Allergy Testing In Eosinophilic Esophagitismentioning
confidence: 99%
“…During a subsequent encounter with the food protein, cross‐linking of IgE on the surface of those cells induces degranulation and release of mediator substances, responsible for the allergic symptoms. However, besides this immediate‐type IgE‐mediated food allergy, in humans there are syndromes mediated by T cells, immunoglobulins other than IgE, or as of yet unknown mechanisms, such as dietary protein enterocolitis syndrome, dietary protein proctitis, dietary protein enteropathy and celiac disease, Dermatitis herpetiformis , food‐induced pulmonary hemosiderosis (Heiner's syndrome), and potentially eosinophilic esophagitis …”
Section: Pathogenesis Of Food Allergymentioning
confidence: 99%